Mediating Spaces: Sound and Hybridity in Installation Practices - Eadie, Jimmy (My University, 2025)
This article will examine the relationship between theories and terms pertaining to Sound Art, Intermediality, Hybrid and Installation Art. These concepts and categories will be examined from the perspective of a practicing sound artist. The paper will look at key artists and theories, to better understand how these terms emerged and how they have influenced the context of discourse between the academy, scholars, and practitioners. A primary concern of the paper is to contextualize the importance of the terminology in light of the increasingly nebulous identification and interpretation of works that use sound as their primary medium. This article is pertinent to the performative arts and digital media cultures, as it offers definitions, literature analyses, and concepts that are central to intermedial and interdisciplinary research and practice.
Art History
Presenting Art History and Theories
PUBLISHED
Nice, France
Keywords: Sound art; Intermedia; Hybrid-Art; Sound Installation